2017
DOI: 10.4103/0973-1075.197952
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of implementing the integrated care plan for the dying in the Indian setting: Survey of perspectives of indian palliative care providers

Abstract: Introduction:Capacity to provide end-of-life care in India is scored as 0.6/100, and very few people in India have access to palliative and end-of-life care. Lack of end-of-life care provision in India has led to a significant number of people receiving inappropriate medical treatment at the end of life, with no access to pain and symptom control and high treatment costs. The International Collaborative for the Best Care for the Dying Person is an initiative that offers the opportunity to apply international e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The initial assessment has a detailed symptom checklist and the ongoing assessment is a brief symptom checklist assessed every 4 h. Any variation in the symptom management is recorded and corrective action is immediately taken. [ 16 ]…”
Section: E Nd Of L Ife C Are In E Nd -S Tage mentioning
confidence: 99%
“…The initial assessment has a detailed symptom checklist and the ongoing assessment is a brief symptom checklist assessed every 4 h. Any variation in the symptom management is recorded and corrective action is immediately taken. [ 16 ]…”
Section: E Nd Of L Ife C Are In E Nd -S Tage mentioning
confidence: 99%
“…[ 1 2 26 ] Education of the medical fraternity at every opportunity through workshops and online courses focusing on opioid availability, accessibility, and training for safe use should be widespread and ongoing. [ 1 26 31 37 ] We need to address the poor public awareness of palliative and end of life care,[ 38 ] so that they come to expect high quality of care.…”
Section: Mplementation Of the A Mendedmentioning
confidence: 99%
“…There is complete lack of uniformity in health-care availability, practices, protocols, standards of care, and access to medications and continuity of care. [ 38 39 40 41 ]…”
Section: Iversity In H Ealth-care mentioning
confidence: 99%
See 1 more Smart Citation
“…Research with Indian patients diagnosed with terminal cancer indicated that pain, physical health, finances, and the future were the most commonly reported concerns. [8] In a recent study,[9] 30 participants from 16 palliative care centers shared their views about the end-of-life care services relevant for the Indian setting. While a majority supported the importance of communication about the dying process and helping patients express their wishes, feelings, beliefs, faith, and values, some participants believed that this was not possible or relevant in the Indian setting.…”
Section: Introductionmentioning
confidence: 99%